Geometrical Shapes in Nepali Panche Baja - Poudel, Gajendra (The Journal of Aadikavi, 2024)
This qualitative research study investigates the existence of geometrical shapes within the traditional Nepali musical ensemble known as panche baja. Panche baja, comprising five primary instruments Nagara (Damaha), Dholaki, Tyamko, Narsingha, and Jhurma (Jhyali or Jhyamta)—is an essential part of Nepali cultural ceremonies, particularly marriages, bratabandha (sacred thread ceremonies), and various religious events. These occasions are significant in Nepalese society, often celebrated with communal participation and marked by traditional music. The Damai community, traditionally responsible for playing panche baja, has preserved these musical practices over generations. The objective of this study was to explore the mathematical aspects embedded in these instruments, specifically focusing on their geometrical features. Using direct observation and analysis, the researcher identified several geometric forms integrated into the structure of panche baja instruments, including circles, parabolas, hemispheres, cylinders, hollow cylinders, parallel lines, and intersecting lines. These shapes are not merely aesthetic but also contribute functionally to the sound quality and durability of the instruments. The findings suggest that mathematical knowledge, particularly an intuitive understanding of geometry, is deeply woven into the traditional craftsmanship of Nepali musical instruments, even though it has been historically undocumented. This study emphasizes the interconnection between traditional art, culture, and mathematics, highlighting the richness of indigenous knowledge systems. Understanding these connections can contribute to broader appreciation and preservation of Nepal’s intangible cultural heritage.